Legal Protection for Consumers Harmed by PT Hasanah Magna Safari's Umrah Services - Azzahra Amalia Wijaya; Faradila Arrahma; Alfia Rahma Nadhifah; Sabrina Mina Nurrahmah (JUSTICES: Journal of Law, 2026)
Hajj and Umrah are very important in the lives of Muslims, especially in Indonesia. However, many pilgrims in Indonesia experience several problems, including fraud and negligence from the Umrah service bureau, especially a case involving PT Hasanah Magna Safari which defrauded hundreds of Umrah pilgrims causing losses of up to 14 billion rupiah. This study aims to analyze consumer protection for Umrah pilgrims, by utilizing a normative legal research approach. This study also examines laws and regulations, Law Number 8 of 1999 and Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah. This study focuses on consumer protection by increasing supervision of Hajj services in Indonesia that can protect consumer rights including the rights of Umrah service bureau pilgrims of PT. Hasanah Magna Safari.